Production of sucroesters using solvent-free reactive systems containing emulsifiers (2018)
The transesterification reaction of sucrose and fatty acid methyl esters to produce sucroesters was experimentally evaluated using commercial emulsifiers as compatibility agents. Reactions were carried out at temperatures between 100 and 140°C, using emulsifier concentrations in the range of 5 to 15 %wt, and potassium carbonate as catalyst. Fatty acid methyl esters consumption and sucroesters production was monitored by HPLC analysis of samples. Methyl esters conversions around 40 % were obtained with 68 %wt monoester content in sucroesters mixture. Despite the reaction times were reduced by operating at high temperatures and high emulsifier’s concentration, multiple substitution and color degradation were observed. Higher productivities of sucroester and higher selectivity to monoesters were obtained when potassium palmitate was used as contacting agent. The lower monoester content in the final product was obtained when using a commercial sucroester emulsifier. Results of this study can be used for preliminary process design in a solvent-free production of biobased sucroesters.